Pengaruh Disiplin Kerja, Budaya Kerja, dan Lingkungan Kerja terhadap Kinerja Pegawai Dinas Sosial, Pemberdayaan Perempuan dan Perlindungan Anak Kota Probolinggo - Noor Farid (Departement of Mathematics Education, 2022)
This study aims to determine the effect of work discipline, work culture, and work environment on the performance of social service employees, women's empowerment and child protection. The research uses a quantitative descriptive research method which is carried out through data collection with primary and secondary data. The data analysis technique in this study is multiple linear regression analysis. The results showed that the variable Work Discipline has a positive and insignificant effect on Employee Performance, meaning that if Work Discipline increases, then Employee Performance will increase, and vice versa. The Work Culture variable has a positive and significant effect on Employee Performance, meaning that if employees have a good Work Culture, then Employee Performance will increase significantly, and vice versa. The work environment variable has a positive and significant effect on employee performance, meaning that if a company has a good work environment, employee performance will increase significantly, and vice versa.